Towards accomplishing millennium development goals (MDGS) in Abuja F.C.T Nigeria: the project management consultants roles - E. A., Ijigah (International Research Association of Computer Science and Technology (IRACST), 2012)
This study examines the prospects and problems of Project Management Consultants in enhancing the Millennium Development Goal in lieu of Cost, Time and Quality of housing projects. Basic literature was reviewed and survey questions were administered while the percentages mean score, critical index and Chi-Square method at 5% level of significance of analysis was used to test data. Among the roles played by project management consultants to enhance housing for the achievement of the millennium development goals are preparation and presentation of project reports to clients periodically (Xn=4.15, Critical Index=0.2769), identification of clients objective (Xn=4.10, Critical Index=0.2735) and coordinating the preparation of as-built drawings for the clients (Xn=4.10, Critical Index=0.2735), The Chi-Square test analyses indicated that the calculated value obtained was (?2 =139.9) against the table value of (?2=16.919) for time overrun, and calculated value obtained was (?2 =128.97) against the table value of (?2=14.067) for cost overrun which revealed that there is significant relationship between the performance of Project Management Consultants and the Cost/Time Duration of MDGs Projects in Abuja FCT. Therefore, Delay by client (Xn=4.41, Critical Index=0.2974), Corruption (Xn=4.31, Critical Index=0.2870) and Variation and Fluctuation (Xn=4.18, Critical Index=0.2786), are factors to be considered during the execution of a project. The study advocates adequate attention to determinants of construction Cost, Time and Quality at the design stage, provision of sufficient finance as at when due and proper reconciliation of client’s and designer’s requirement to prevent duration overrun of such significant national projects.